Mechanistic Origin of Photoredox Catalysis Involving Iron(II) Polypyridyl Chromophores - Woodhouse, Matthew D; McCusker, James K (Journal of the American Chemical Society, 2020)
Photoredox catalysis employing ruthenium- and iridium-based chromophores have been the subject of considerable research. However, the natural abundance of these elements are among the lowest on the periodic table, a fact that has led to an interest in developing chromophores based on earth-abundant transition metals that can perform the same function. There have been reports of using FeII-based polypyridyl complexes as photocatalysts, but there is limited mechanistic information pertaining to the nature of their reactivity in the context of photoredox chemistry. Herein, we report the results of bimolecular quenching studies between [Fe(tren(py)3)]2+ (where tren(py)3 = tris(2-pyridyl-methylimino-ethyl)amine) and a series of benzoquinoid acceptors. The data provide direct evidence of electron transfer involving the lowest-energy ligand-field excited state of the Fe(II)-based photosensitizer, definitively establishing that Fe(II) polypyridyl complexes can engage in photoinduced redox reactions but by a mechanism that is fundamentally different than the MLCT-based chemistry endemic to their second- and third-row congeners.